Antimicrobial activity of Averrhoa bilimbi fruit extracts against foodborne bacteria / by Hazirah bt Abd Azhar - Abd Azhar, Hazirah (2016)
Averrhoa bilimbi, locally known as Belimbing buluh belongs to family Oxalidaceae are commonly consumed and widely cultivated in Malaysia. A. bilimbi fruit has been used as traditional remedies to cure fever, coughs, inflammation, diabetes and hypertension This study was undertaken to determine the potential of A. bilimbi fruits extracts as natural antibacterial against foodborne pathogens which are Staphylococcus aureus (ATCC 25923), Bacillus cereus (ATCC 11788), Escherichia coli (ATCC 25922) and Salmonella typhimurium (ATCC 14028). Screening of antimicrobial activity of aqueous and ethanolic extracts of A. bilimbi fruits were done using disk diffusion method. Concentration of 1000 µg/ml of the extracts were diffused into blank filter paper disc and placed onto cultured agar. The preliminary screening for both extracts showed inhibition activity against all tested bacteria. The Minimum Inhibitory Concentration (MIC) was performed by using microdilution broth method. The MIC value of aqueous extract are the same for all organism tested which is 62.5 µg/ml. The MIC value of ethanol extract is 62.5 µg/ml for S. aureus, E. coli and S. typhimurium while B. cereus showed slightly lower MIC value which is 31.25 µg/ml. The Minimum Inhibitory Concentration (MBC) was done to confirm the MIC value. All tested organism showed the same MBC value when treated with aqueous extract which is 125 µg/ml. The MBC value of ethanol extract is 125 µg/ml for S. aureus, E. coli and S. typhimurium while B. cereus showed lower MIC value which is 62.5 µg/ml. In conclusion, this study proved that A. bilimbi fruit extract possess antimicrobial activity against selected foodborne bacteria.